2018
DOI: 10.1097/jom.0000000000001433
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Bullying and Psychological Distress

Abstract: The results of the current study suggest that the presence of bullying in the workplace can have a detrimental effect on employees' mental health even if they are not personally victimized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…We assessed turnover intention as a potential consequence and used three items developed by Geurts et al (1998), translated into Japanese, and validated (Tsuno et al, 2018). Originally, this scale consisted of four items -three items were negatively worded, and one was positively worded and reverse-scored.…”
Section: Potential Consequencesmentioning
confidence: 99%
“…We assessed turnover intention as a potential consequence and used three items developed by Geurts et al (1998), translated into Japanese, and validated (Tsuno et al, 2018). Originally, this scale consisted of four items -three items were negatively worded, and one was positively worded and reverse-scored.…”
Section: Potential Consequencesmentioning
confidence: 99%
“…While various types of work-related events such as disasters, interpersonal conflict in the workplace, and job characteristics (Tsuno et al 2018;Pennington et al 2018;Nishimura et al 2020;Gerhardt et al 2021) have been identified as risk factors for workers' mental health, the association between long working hours and workers' mental health is still contentious. During the IACI investigation for compensation determination, the existence and severity of 36 types of work-related events, including interpersonal conflict and overtime work, were evaluated as possible backgrounds for mental disorders (Nishimura et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…One article in the English‐language investigated gender, sexual, and academic harassment among university faculties and demonstrated that women who have seen or heard of someone who experienced harassment had higher burnout scores even though they were not direct victims of any harassment 43 . A longitudinal study also revealed that division‐level workplace bullying was associated with increased individual‐level psychological distress in the public sector with 3142 employees 44 . These results suggest that harassment or bullying in the workplace can have a detrimental effect on employees' mental health even if they are not personally and directly victimized.…”
Section: Resultsmentioning
confidence: 99%